Healthcare costs associated with language difficulties up to 9 years of age: Australian population-based study - Sciberras, E; Nicholson, J; Westrupp, E; Reilly, S; Mensah, F; Lucas, N; Wake, M; Gold, L (My University, 2014)
ABSTRACT This study aimed to quantify the non-hospital healthcare costs associated with language difficulties within two nationally representative samples of children. Data were from three biennial waves (2004-2008) of the Longitudinal Study of Australian Children (B cohort: 0-5 years; K cohort: 4-9 years). Language difficulties were defined as scores ≤ 1.25 SD below the mean on measures of parent-reported communication (0-3 years) and directly assessed vocabulary (4-9 years). Participant data were linked to administrative data on non-hospital healthcare attendances and prescription medications from the universal Australian Medicare subsidized healthcare scheme. It was found that healthcare costs over each 2-year age band were higher for children with than without language difficulties at 0-1, 2-3, and 4-5 years, notably 36% higher (mean difference = $AU206, 95% CI = $90, $321) at 4-5 years (B cohort). The slightly higher 2-year healthcare costs for children with language difficulties at 6-7 and 8-9 years were not statistically different from those without language difficulties. Modelled to the corresponding Australian child population, 2-year government costs ranged from $AU1.2-$AU12.1 million (depending on age examined). Six-year healthcare costs increased with the persistence of language difficulties in the K cohort, with total Medicare costs increasing by $192 (95% CI = $74, $311; p = .002) for each additional wave of language difficulties. In conclusion, language difficulties (whether transient or persistent) were associated with substantial excess population healthcare costs in childhood, which are in addition to the known broader costs incurred through the education system. It is unclear whether healthcare costs were specifically due to the assessment and/or treatment of language difficulties, as opposed to conditions that may be co-morbid with or may cause language difficulties.
International Journal of Speech-Language Pathology
Keywords: Child Development -- Speech and Language; Children; Health; Children -- Early childhood; Childhood and child development; Health and wellbeing; Children; Health; Child Development; Early childhood; Speech and Language; Childhood and child development; Health and wellbeing